Characteristics of Arctic tides at CANDAC-PEARL (80 degrees N, 86 degrees W) and Svalbard (78 degrees N, 16 degrees E) for 2006-2009 : radar observations and comparisons with the model CMAM-DAS - Manson, Alan; Meek, Chris; Xu, X.; Aso, Takehiko; Drummond, J. R.; Hall, Chris; Hocking, W. K.; Tsutsumi, Masaki; Ward, W. E. (Annales Geophysicae, 2011)
Operation of a Meteor Radar (MWR) at Eureka, Ellesmere Island (80° N, 86° W) began in February 2006: this is the location of the Polar Environmental and Atmospheric Research Laboratory (PEARL), operated by the "Canadian Network for the Detection of Atmospheric Change" (CANDAC). The first 36 months of tidal wind data (82–97 km) are here combined with contemporaneous tides from the Meteor Radar (MWR) at Adventdalen, Svalbard (78° N, 16° E), to provide the first significant evidence for interannual variability (IAV) of the High Arctic's diurnal and semidiurnal migrating (MT) and non-migrating tides (NMT). The three-year monthly means for both diurnal (DT) and semi-diurnal (SDT) winds demonstrate significantly different amplitudes and phases at Eureka and Svalbard. Typically the summer-maximizing DT is much larger (~24 m s−1 at 97 km) at Eureka, while the Svalbard tide (5–24 m s−1 at 97 km)) is almost linear (north-south) rather than circular. Interannual variations are smallest in the summer and autumn months. The High Arctic SDT has maxima centred on August/September, followed in size by the winter features; and is much larger at Svalbard (24 m s−1 at 97 km, versus 14–18 m s−1 in central Canada). Depending on the location, the IAV are largest in spring/winter (Eureka) and summer/autumn (Svalbard). Fitting of wave-numbers for the migrating and non-migrating tides (MT, NMT) determines dominant tides for each month and height. Existence of NMT is consistent with nonlinear interactions between migrating tides and (quasi) stationary planetary wave (SPW) S=1 (SPW1). For the diurnal oscillation, NMT s=0 for the east-west (EW) wind component dominates (largest tide) in the late autumn and winter (November–February); and s=+2 is frequently seen in the north-south (NS) wind component for the same months. The semi-diurnal oscillation's NMT s=+1 dominates from March to June/July. There are patches of s=+3 and +1, in the late fall-winter. These wave numbers are also consistent with SPW1-MT interactions. Comparisons for 2007 of ...